Analysis of Class III Skeletal Malocclusion that Require Orthognathic Surgery for Correction as Compared to Camouflage Treatment - A Retrospective Study - Swapna Sreenivasagan1 , Aravind S Kumar2 , SriRengalakshmi3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Class III malocclusion is a complex anomaly . Not all adult class III patients will need surgical correction.In the Indian population the incidence of a class III malocclusion is lesser than a class II. Orthodontic caserecords were reviewed and analysed. Class III adult malocclusions were evaluated to estimate the prevalenceand the treatment protocol. From this evaluation of class III patients the span on close to a year report of 44adult class III patients out of whom 10 patients required orthognathic surgery for correction . Surgery firstdone in 2 cases and other cases were single jaw or bi-jaw surgery done using conventional approach.In thecamouflage treatment most of the cases were treated by non- extraction. Correct classification of adult ClassIII malocclusion patients succeeded to a high degree. Pearson’s chi-square value is 1.867 and P value is 0.1and the results of this study are not significant. The severity of the malocclusion should be used to determinethe treatment protocol.Orthognathic surgery was successful in 92% patients . Most of the camouflage studiesuse mini-implants and non-extraction protocols. Surgical treatment done according to severity of class IIIand patient compliance.Among the assessed population 44 patients had skeletal class III malocclusion andin the adult patients 8 patients were treated with orthognathic surgery . The two main deciding factors toconclude as the treatment plan was based on the severity of the malocclusion and the patient compliance.Orthognathic surgery was successful in 92% patients